Development of Interactive Multimedia Through Realistic Mathematics Education Approach Assisted by Articulate Storyline - Wahyuni, Fina Tri; Adiyanto, A. Sahrul; Syifa, Zahra As (Jurnal Pendidikan Matematika, 2025)
The purpose of this research is to develop interactive multimedia based on the Realistic Mathematics Education (RME) approach with Articulate Storyline, on the topic of Systems of Linear Equations in Two Variables (SPLDV), and to determine the validity and practicality of the product. This research employed the Research and Development (R&D) method using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). A small-scale trial involved with six students, and a large-scale trial was conducted with 26 eighth-grade students from MTs Urwatil Wutsqo Jepara. The results indicated that the interactive multimedia based on the RME approach supported by Articulate Storyline for SPLDV was highly valid and very practical for instructional use. The Evaluation by content experts resulted in an overall percentage score of 86.25% in the "highly valid" category. The assessment from media experts received an overall percentage score of 95% in the "highly valid" category. Additionally, the validation of the student response questionnaire experts obtained a percentage score of 87% in the "highly valid" category. The small-scale trial achieved a score of 83.33% in the "very practical" category, while the large-scale trial received a percentage score of 87% in the "very practical" category. This research provides an alternative for media developers to design digital teaching materials that are both interactive and mathematically meaningful. In addition, it can increase student engagement, especially in understanding abstract mathematical concepts. This study opens opportunities for future research on developing interactive multimedia using more flexible or AI-based platforms as innovative tools to enhance the quality of mathematics education. Tujuan penelitian yaitu mengembangkan multimedia interaktif melalui pendekatan Realistic Mathematics Education (RME) berbantuan Articulate Storyline pada materi Sistem Persamaan Linear Dua Variabel (SPLDV) serta mengetahui kevalidan dan dan kepraktisan produk tersebut. Penelitian menggunakan metode Research and Development (R&D) dengan model pengembangan ADDIE (Analysis, Design, Development, Implementation, Evaluation). Pada tahap uji coba skala kecil pada 6   peserta didik dan uji coba skala besar dilakukan pada 26 peserta didik kelas VIII MTs Urwatil Wutsqo Jepara. Hasil penelitian menunjukkan bahwa multimedia interaktif melalui pendekatan RME berbantuan Articulate Storyline pada materi SPLDV dalam kategori sangat valid dan sangat praktis digunakan dalam pembelajaran. Penilaian dari ahli materi secara keseluruhan memperoleh nilai presentase 86,25% dengan kategori “sangat valid”. Sedangkan penilaian dari ahli media secara keseluruhan memperoleh nilai presentase sebesar 95% dengan kategori “sangat valid”. Selanjutnya hasil validasi oleh ahli angket respon peserta didik memperoleh nilai presentase sebesar 87% dengan kategori “sangat valid”. Hasil uji coba skala kecil memperoleh nilai presentase 83,33% dengan kategori “sangat praktis”. Pada uji coba skala besar memperoleh nilai presentase sebesar 87% dengan kategori “sangat praktis. Implikasi dari penelitian ini yaitu memberikan alternatif bagi pengembang media untuk menciptakan bahan ajar digital yang tidak hanya interaktif tetapi juga bermakna secara matematis. Selain itu dapat meningkatkan keterlibatan siswa, terutama dalam memahami konsep-konsep abstrak matematika. Penelitian ini membuka peluang bagi studi lanjutan mengenai pengembangan multimedia interaktif dengan platform lain yang lebih fleksibel atau berbasis AI dapat dijajaki sebagai inovasi untuk meningkatkan kualitas pembelajaran matematika di masa depan.